CHARACTERIZATION OF THE IONIC AND PARTICULATE SYSTEMS IN THE RESERVOIR - Moreton Godoi, Ricardo Henrique; Lima Bittencourt, Andre Virmond; Hirata, Patricia Yassumoto; Jafelicci Junior, Miguel [UNESP]; Reis Neto, Jose Manoel dos; van Grieken, Rene; Carneiro, C.; Andreoli, C. V.; Cunha, CLN; Gobbi, E. F. (Iwa Publishing, 2014)
Suspended particles, as well as dissolved substances, have an important ecological role in water quality by attenuating light, providing reactive surfaces, influencing metabolic activity, and contributing to sediment deposition. The quality of water, particularly in reservoirs, is crucial and is naturally maintained by circulation and sedimentation, which removes phosphorus from the water, for example. In eutrophic reservoirs, these processes are contrasted by the recycling of ions and metals coming from sediments, which can maintain or neutralize the state of eutrophication. The combination of trace elements and microanalysis techniques may be useful in the context of tracking anthropogenic or natural activities close to a water body. These may be used to trace the sources of pollution by means of a chemical fingerprint of such heterogeneous materials, for example, particles in suspension. The magnitude and patterns of ion, metal and particulate systems were evaluated at the Rio Verde Reservoir. Samples were analyzed through energy-dispersive X-ray fluorescence (EDXRF), ion chromatography (IC), inductively coupled plasma - mass spectrometry (ICP-MS), and particle size distribution via Laser and Zeta Potential. Based on the results, the chemical patterns are discussed in relation to heavy metal concentration, suspended matter and ion composition.
Keywords: Reservoir; ICP; zeta potential; x-ray fluorescence; particulate matter